2008
DOI: 10.1007/s11524-008-9256-0
|View full text |Cite
|
Sign up to set email alerts
|

Sampling and Recruitment in Multilevel Studies among Marginalized Urban Populations: The IMPACT Studies

Abstract: Illicit drug use in urban settings is a major public health problem. A range of individual level factors are known to influence drug use and its consequences, and a number of recent studies have suggested that the neighborhood in which an individual lives may also play a role. However, studies seeking to identify neighborhood-level determinants of drug use, particularly among marginalized urban populations, need to overcome significant challenges, particularly in the area of sampling and recruitment. One key i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Baseline survey data were collected beginning in early The street-intercept survey methodology has been shown to produce a more representative sample than traditional sampling methods when trying to reach a low-income, difficult-to-contact population (24,25) . Street-intercept surveys have also been successfully implemented in several other studies looking at food environments in low-income neighbourhoods (26)(27)(28)(29) and thus were chosen as a reliable means of recruitment for the present study.…”
Section: Data Collectionmentioning
confidence: 99%
“…Baseline survey data were collected beginning in early The street-intercept survey methodology has been shown to produce a more representative sample than traditional sampling methods when trying to reach a low-income, difficult-to-contact population (24,25) . Street-intercept surveys have also been successfully implemented in several other studies looking at food environments in low-income neighbourhoods (26)(27)(28)(29) and thus were chosen as a reliable means of recruitment for the present study.…”
Section: Data Collectionmentioning
confidence: 99%
“…For example, researchers could conduct street-intercept surveys with individuals in neighborhoods as previous research has shown that this particular survey method can yield more representative samples when compared to traditional sampling methods (e.g. random digit dialing) (Miller et al, 1997;Ompad et al, 2008) and then aggregate responses to a neighborhood unit for analyses. Furthermore, there is an additional research opportunity to psychometrically develop an instrument of spatial stigma that would assist in these types of research investigations.…”
Section: Discussionmentioning
confidence: 99%
“…As such, diverse but complementary approaches to participant recruitment, such as those used in this study, are recommended for recruiting hard to reach or hidden populations (Ompad et al, 2008).…”
Section: Establishing Network For Participant Recruitmentmentioning
confidence: 99%